Prophecy pros illustrated guide to tough questions about the end times - Kinley, Jeff (Harvest House Publishers, 2021)
The basics of Bible prophecy -- The different views -- The rapture/appearing -- The rapture -- The Jewish people/Israel -- The tribulation period -- The Antichrist -- The physical return of Christ -- The literal Kingdom -- The eternal state.